DONGGALA: FROM IMPERALISM TO THE REGENCY ESTABLISHMENT - Lukman Nadjamuddin; Idrus Idrus (ISTORIA: Jurnal Pendidikan dan Sejarah, 2008)
AbstractThe Effort exerted by the Dutch to conquer Banawa Kingdom, particularly Donggala City, began with the assumption derived from economic and political calculation that the confiscation would make it possible for the Dutch to pacify its trade channel in Makasar narrows and extend economic exploitation, given that Donggala had a strategic port, related to the chain of Archipelago’s trade. The method of confiscation-friendship relation was not realized because resistances, in the form of physical attack- began to come forward. In Donggala, Molanda played a role as the main actor in the rebellion. In Sigi, Toma I Dompo consistently attacked, both after and before arrested in Sukabumi. In Sojol, Toma Tarima along with his son assailed the Dutch and in Kulawi, Toma Itorengke set about the Dutch as well.During  the  Japanese  imperialism,  the  education  system  of      the  Dutch  waseliminated, and replaced with Japanese education which required to speak Japanese and Indonesia languages, to sing Kimigayo, to give respect to Hinomaru, to do Seikrei, Kinrohosyi and Taiso. The social and political organization was limited, while those which supported the mass mobilization were established, such as Seinendan. This led the nationalists to do the underground movement. In the agriculture, native people were obligated to plant cotton, rice, corn and cassava as to overcome the lack of food and clothing.After the independence was announced, Donggala faced by two struggle NICAattack and to establish the Donggala Regency. The effort to maintain the freedom was conducted  in  two  ways,  physical  struggle  and           establish           of  social  and  political organization,  while  the  establishment  of  Donggala  Regency  gained  two  important momentum; the establishment of Administrative region of Donggala on the basis of Sulawesi Governor’s verdict no. 633 on October 25th, 1951 and the establishment of Donggala Regency on the basis of Government regulation no.33 on August 12th.1952. Keyword: Donggala, Imperialism, Regency.